A new cryptic species of Pithecopus (Anura, Phyllomedusidae) in north-eastern Brazil - de Andrade, Felipe Silva; Haga, Isabelle Aquemi; Ferreira, Johnny Sousa; Recco-Pimentel, Shirlei Maria; Toledo, Luís Felipe; Bruschi, Daniel Pacheco (European Journal of Taxonomy, 2020)
The genus of Neotropical frogs Pithecopus includes 11 species occurring east of the Andes from southern Venezuela to northern Argentina. Recent genetic approaches pointed out an unusual genetic diversity among populations from localities in north-eastern Brazil recognized as P. nordestinus. In fact, one of these studies confirmed the hypothesis that the São Francisco River acted as an effective geographical barrier during vicariant events in the evolutionary history of P. nordestinus, resulting in two principal, highly divergent clades. Herein we formally describe this divergent clade as a new cryptic species of Pithecopus from north-eastern Brazil, the sister clade of P. nordestinus. It differs from other species of Pithecopus, except for P. azureus and P. nordestinus, by its small body size, lack of the reticulate pattern on flanks, smaller head width, and advertisement calls generally composed of a three-pulsed core.